Investigating the Effects of Sport-Metric Training on Functional Factors Related to Lower Limb Injuries and Skill Variables in Young Futsal Players - Mohammad Kalantariyan; Sirvan Zarghami Aliabad; Jamal Khalandi (Biyumikānīk-i varzishī)
Objective The present study aimed to examine the effects of injury prevention training using the Sport-Metric method on functional factors associated with reducing the risk of lower extremity injuries, as well as skill-related variables in young futsal players. Methods This study employed a quasi-experimental design. The participants included 30 futsal players aged 9 to 12 years who met the inclusion and exclusion criteria. They were randomly assigned to two groups of 15: an experimental group and a control group. Before and after six weeks of Sport-Metric training, agility, static balance, dynamic balance, power, dribbling speed, and shooting accuracy were assessed using the Illinois Agility Test, Stork Test, Y-Balance Test, Triple Hop Test, Dribbling Test, and Moore-Christian Shooting Test, respectively. The experimental group performed Sport-Metric-specific exercises for six weeks, three sessions per week, while the control group continued their routine futsal training. Data analysis was conducted using paired t-tests and analysis of covariance (ANCOVA) at a significance level of 0.05. Results The ANCOVA results indicated significant differences between the experimental and control groups after six weeks of training in agility performance (p = 0.001), static balance (p = 0.001), dynamic balance (p = 0.005), power (p = 0.003), dribbling speed (p = 0.013), and Moore-Christian shooting accuracy (p = 0.001). Conclusion The findings of this study demonstrate that Sport-Metric training can significantly enhance both the physical and skill-related abilities of young futsal players. Therefore, it is recommended that Sport-Metric training be incorporated as an effective and practical approach in youth futsal development programs.